On the Edge of Chaos: Irreversible Consequences of the Power Legitimacy Rupture - Vinnykova, N. (My University, 2017)
Considering political decision-making as the core of power implementation process, this paper suggests that the lack of legitimacy of the concrete political decisions can be a strong reason for the scenario of social frustration tendencies. The article introduces the notion of ‘legitimacy rupture’, i.e. irreversible process of the power delegitimation, that can emerge when a tension between the power-holders and society, and the inter-network disagreement inside the ruling elite regarding the decision-making, are simultaneously take place. We state that under the present conditions of the tight cross-nationalization and a legitimacy rupture in any one political system is an extremely dangerous phenomenon as it can cause a state of turbulence on a large scale, and entails unexpected consequences for concrete actors, their internal and external policies, as well as for the international system on the whole. Thus, the article refer to the analytical categories of the chaos theory and nonlinear systems when studying conditions and consequences of power delegitimation or building scenarios of/for potential one. In respect to methodological principles of the chaos theory on the examples of conflict situation in Syria and Ukraine, we illustrate how legitimacy rupture in particular cases of decision-making transformed into bifurcation points and caused uncontemplated consequences overwhelming its primary targets and scope. In order to articulate the validity of studying power delegitimation through chaos theory explications the study reveals that the current social and political trends of post-democratic development directly or indirectly effect the entropy growth.
Keywords: political decisions; power delegitimation; chaos; entropy; Syria; Ukraine